2012
DOI: 10.1371/journal.pone.0031635
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Exposure to a Mer Ligand in Leukemia: Gas6 Favors Expression of a Partial Mer Glycoform and Reveals a Novel Role for Mer in the Nucleus

Abstract: Mer tyrosine kinase is ectopically expressed in acute lymphoblastic leukemia and associated with enhanced chemoresistance and disease progression. While such effects are generally ascribed to increased engagement of oncogenic pathways downstream of Mer stimulation by its ligand, Gas6, Mer has not been characterized beyond the scope of its signaling activity. The present study explores Mer behavior following prolonged exposure to Gas6, a context similar to the Gas6-enriched microenvironment of the bone marrow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 46 publications
(65 reference statements)
0
32
0
3
Order By: Relevance
“…Although the role of Mer as an extracellular receptor and promoter of intracellular signal transduction has been previously reported, Mer has also been found to internalize and localize to the nucleus, 35 suggesting that it may have a role in regulation of gene expression. Comparison of transcriptional differences between our control and Mer knockdown B-ALL cells after treatment with Gas6 or methotrexate demonstrated decreased prosurvival BCL-XL, PI3K, and PKC expression and increased proapoptotic BAX, NOXA, and PUMA expression in the knockdown cells, further demonstrating a survival advantage of lymphoblast signaling through Mer.…”
Section: Discussionmentioning
confidence: 97%
“…Although the role of Mer as an extracellular receptor and promoter of intracellular signal transduction has been previously reported, Mer has also been found to internalize and localize to the nucleus, 35 suggesting that it may have a role in regulation of gene expression. Comparison of transcriptional differences between our control and Mer knockdown B-ALL cells after treatment with Gas6 or methotrexate demonstrated decreased prosurvival BCL-XL, PI3K, and PKC expression and increased proapoptotic BAX, NOXA, and PUMA expression in the knockdown cells, further demonstrating a survival advantage of lymphoblast signaling through Mer.…”
Section: Discussionmentioning
confidence: 97%
“…Related to the concept of receptor trafficking, a recent study found MERTK to be located not only at the cell surface, but also in the nucleus. Consensus nuclear localization sequences have also been identified in the MERTK gene (52). This raises the possibility that MERTK may have effects on gene transcription.…”
Section: Mertk Migration and Cellular Trafficmentioning
confidence: 97%
“…The multiple MERTK species observed are likely due to posttranslational modifications, most notably, glycosylation. MERTK has been described to be both heavily and differentially glycosylated through Asn-linked glycosylation (23,24). Treatment of melanoma cell lysates with PNGase F resulted in 1 predominant lower molecular weight band (Supplemental Figure 2).…”
Section: Figurementioning
confidence: 99%